Laparoendoscopic Single-Site Technique Contrasted with Conventional Laparoscopy in Cystectomy for Benign Ovarian Cysts - Xinru Jiang, MM; Xin Zuo, MM; Hongdi Zhu, MM (Elsevier, 2023)
ABSTRACT: Objective: To compare the laparoendoscopic single-site (LESS) technique with conventional laparoscopy in cystectomy for benign ovarian cysts. Materials and methods: A retrospective analysis was performed at Yixing People's Hospital from April 2020 until December 2021. Results: Thirty-seven patients using the LESS technique were compared with a control group of 45 patients who underwent a traditional laparoscopic ovarian cystectomy. There was no statistically significant difference in the perioperative hemoglobin level changes, cyst rupture rate, postoperative recovery of exhausting time, or pain score at 24 hours after surgery between the 2 groups (P > 0.05). The mean operating time was significantly longer in the LESS group than that of the control group (88.38 ± 30.57 minutes vs 59.44 ± 24.22 minutes; P = 0.001). However, the length of postoperative hospital stay was significantly shorter in the LESS group (3.70 ± 0.57 days vs 4.38 ± 0.86 days; P = 0.001). In addition, total hospitalization expenses were higher in the LESS group (14,709.78 ± 1618.63 yuan vs 12,676.73 ± 1411.78 yuan; P = .001) and the satisfaction score was also significantly higher in the LESS group (z = -2.272; P = 0.023). After a follow-up time of 12 to 24 months, no patient in either group showed wound infection, umbilical hernia, or recurrent cysts. Conclusions: The LESS technique for benign ovarian cystectomy is safe, feasible, and equally effective compared with the multiport laparoscopic oophorocystectomy. Although it currently costs more, patients with benign ovarian cysts are highly satisfied with the LESS technique.